Global Effects of COVID-19, government restrictions and implications for sex workers: A focus on Africa. (2020) - Campbell, Rosie; Sanders, Teela; Hassan, Rahma; Gichuna, Susan; Mutonyi, Mercy; Mwangi, Peninah
No abstract available